Specialisation and/or Convergence: Structure of European Exports and Production - Ville Kaitila (The Research Institute of the Finnish Economy (ETLA), 2013)
We analyse the degree of EU countries' specialisation in their exports and manufacturing value added using the Herfindahl-Hirschmann index and the degree of structural similarity using the similarity index developed by Finger and Kreinin (1979). We also analyse the convergence of GDP growth rates over time and compare it with export similarity. At the industry level (HS2), EU15 countries' exports became more specialised before the introduction of the euro and less specialised thereafter. However, exports have become more specialised at the product level (HS6) during the euro years. Manufacturing value added (21 sectors) has become more specialised both before and after 1999. The results for the ten ex-transition countries' exports are different reflecting their economic transformation. Also the post-2008 period with economic distress creates special cases. Export structures became more similar before 2008. However, manufacturing value added similarity decreased. GDP growth rates have been more uniform after the introduction of the euro than in 1992–1999. We find that similarity in export structures is positively associated with the degree of GDP growth rate correlation vis-à-vis the Euro Area average. There are a half a dozen outliers that differ in their GDP growth developments, among them the Euro Area members Greece, Malta and Slovakia
Keywords: F14; F15; F44; 330; Exports; manufacturing; specialisation; similarity; GDP growth